2017
DOI: 10.1111/socf.12359
|View full text |Cite
|
Sign up to set email alerts
|

Can Cameras Stop the Killings? Racial Differences in Perceptions of the Effectiveness of Body‐Worn Cameras in Police Encounters,

Abstract: Recent killings of blacks by police have renewed a national discussion about crime, racism, unjust treatment, and implicit bias. Outfitting police officers with body-worn cameras (BWC) is heralded by federal and state lawmakers as one solution to providing more transparency during police encounters. Missing from this discussion is what everyday citizens think about the potential effectiveness of BWC. Using data on residents of Prince George's County, Maryland, this study explores racial differences in views ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 36 publications
0
37
0
1
Order By: Relevance
“… Editor's Note : This article is part of a special issue of Sociological Forum titled “Whose Lives Matter? Violence, Social Control, and the Racial Divide.” For other articles featured in the issue, see Auyero and Sobering (2017), Carter, Parker and Zaykowski (2017), Cerulo (2017), Henricks and Harevy (2017), LeCount (2017), Ray, Marsh, and Powelson (2017), Roschelle (2017), Ruane (2017), Scarborough (2017), Sykes, Piquero, and Gioviano (2017), and Torres, Cannito‐Coville, and Rodriguez (2017). …”
mentioning
confidence: 99%
“… Editor's Note : This article is part of a special issue of Sociological Forum titled “Whose Lives Matter? Violence, Social Control, and the Racial Divide.” For other articles featured in the issue, see Auyero and Sobering (2017), Carter, Parker and Zaykowski (2017), Cerulo (2017), Henricks and Harevy (2017), LeCount (2017), Ray, Marsh, and Powelson (2017), Roschelle (2017), Ruane (2017), Scarborough (2017), Sykes, Piquero, and Gioviano (2017), and Torres, Cannito‐Coville, and Rodriguez (2017). …”
mentioning
confidence: 99%
“…In 2017, we published results from a large study on body‐worn cameras (Ray, Marsh, et al 2017). We conducted interviews with residents of Prince George’s County, Maryland.…”
Section: Limits Of Existing Policies Without Restructuring Civilian Pmentioning
confidence: 99%
“…BWCs may impact public perceptions of police legitimacy (both positively and negatively), particularly in marginalized communities. Ray, Marsh, and Powelson (2017) found that racialized groups are less likely to believe implementation of BWCs will make police more accountable or transparent. In this way, BWCs may act as tools that entrench antagonistic relations with marginalized communities.…”
Section: Critical Reflections On the Effects Of Body-worn Cameras On mentioning
confidence: 99%